Good sex : transforming America through the new gender and sexual revolution - Roach, Catherine M., 1965- (Indiana University Press, 2022)
"The United States may have a puritanical past, but the 21st century is wide open to diverse gender expression and romance. Good Sex is the manifesto-or ManiSexto, if you will-for this cultural revolution. Same-sex marriage is legal, the #MeToo movement has exploded, colleges nationwide now teach consent-based sexual health, the media celebrates body positivity, and transgender visibility has become mainstream. Defining "good sex" as both ethical and pleasurable, Catherine M. Roach features such topics as equity, intersectionality, and shared pleasure while offering a lively discussion that is inclusively feminist, queer-friendly, and sex-positive without being divisive. An accessible guidebook, Good Sex provides hope that America's sexual, gender, and racial injustices can be addressed together. After all, this new gender and sexual revolution strengthens the pursuit of happiness and love. Welcome to the revolution!"--